Photovoltaic-powered Membrane Desalination in Urban and Rural Areas - Ghermandi, Andrea; Batayneh, Sakhaer (Annals of Arid Zone, 2016)
The integration with 'renewable energy sources is a key area of development in the desalination sector for its potential to reduce the environmental footprint of the energy-thirsty state-of-the-art technologies and bring sustainable development to remote, arid areas lacking access to inexpensive electric energy. In light of the recent market trends, which indicate a rapid gain in market shares by membrane technologies at the expense of thermal processes, this study critically evaluates the research and field experience with coupling photovoltaic power and membrane desalination, with a focus on reverse osmosis, nanofiltration and electrodialysis processes. The results suggest that photovoltaic-powered membrane desalination is technologically well developed and mature for gaining larger shares in the desalination market where the conditions are favorable, i.e., for small and medium-scale applications in remote regions. Two case-study examples are presented discussing the feasibility of solar desalination for the production of drinking water in an urban area in Jordan and of irrigation water in a remote rural community in Israel. Key words: Electrodialysis, membrane desalination, nanofiltration, photovoltaic, renewable energy, reverse osmosis, solar energy.